Analisis Pengaruh Pertumbuhan Ekonomi, Upah Minimum dan Indeks Pembangunan Manusia Terhadap Tingkat Penganggruan di Provinsi Sumater Utara - Aisyaturridho; Ahmad Albar Tanjung; Weni Hawariyuni (Jurnal Samudra Ekonomika, 2021)
Aisyaturridho. Analysis of the Effect of Economic Growth, Minimum Wages and Human Development Index on Unemployment Rate in North Sumatra. Thesis. Medan: Postgraduate Program at the University of North Sumatra, 2021. Unemployment is a problem that must be faced by North Sumatra. The Open Unemployment Rate in North Sumatra in 2017-2020 is still fluctuating. This study aims to test empirically the effect of economic growth, minimum income and the human development index (IPM) on the open unemployment rate in North Sumatra. This study uses time series and cross section data from 2017 to 2020 from BPS North Sumatra. For data analysis using Panel Data Analysis Method which is based on data processing using the software program E-views 10. The results showed a value of R2 is 0.94. This means that 94% of the proportion of the independent variables used is able to explain the variation in the dependent variable in the model, while the remaining 6% is explained by other variables not used in this study. All independent variables have a P-value less than 0.05. This means that all the independent variables used in the estimation of this analysis model, namely economic growth, minimum income and the human development index (IPM) together have a significant effect on unemployment in North Sumatra. The significant economic growth variable has a negative effect on the open unemployment rate in North Sumatra, has a p-value of 0.0001 with a regression coefficient is -24.14609 which means that every 1 billion rupiah increase in economic growth will reduce 24.14609% of the open unemployment rate. The minimum income variable has a significant positive effect on the open unemployment rate in North Sumatra which has a p-value of 0.0005 with a regression coefficient of 8.005012, meaning that if there is an increase of 1 million rupiah the minimum income will increase 8.005012% of the open unemployment rate. Meanwhile, the human development index variable has a significant positive effect on the open unemployment rate in North Sumatra because the p-value is 0.0454 with a regression coefficient of 0.997629 which means that if the human development index increases by 1 ratio, it will increase the open unemployment rate by 0.997629%. To reduce the open unemployment rate, the government must increase the economic growth and human development index, while the minimum income must be stabilized in order to reduce the open unemployment rate. Keywords: Open Unemployment Rate, Economic Growth, Minimum income, Human Development Index (IPM).